2014
DOI: 10.1007/s00466-014-1027-z
|View full text |Cite
|
Sign up to set email alerts
|

Density and level set-XFEM schemes for topology optimization of 3-D structures

Abstract: As the capabilities of additive manufacturing techniques increase, topology optimization provides a promising approach to design geometrically sophisticated structures which can be directly manufactured. Traditional topology optimization methods aim at finding the conceptual design but often lack a sufficient resolution of the geometry and structural response, needed to directly use the optimized design for manufacturing. To overcome these limitations, this paper studies the viability and characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 46 publications
(56 reference statements)
4
49
0
Order By: Relevance
“…Nguyen et al (2012) obtained an open-walled frame-like structure which must be attributed to the coarse mesh used for the study. Villanueva and Maute (2014) studied the same problem and found that with mesh refinement the optimized structure goes from being frame-like to being closed-walled -fully in agreement with the findings of the present paper.…”
Section: D Torsion Rodsupporting
confidence: 89%
“…Nguyen et al (2012) obtained an open-walled frame-like structure which must be attributed to the coarse mesh used for the study. Villanueva and Maute (2014) studied the same problem and found that with mesh refinement the optimized structure goes from being frame-like to being closed-walled -fully in agreement with the findings of the present paper.…”
Section: D Torsion Rodsupporting
confidence: 89%
“…The simplest way is using the concept of ersatz material on the elements cut by the zero level curve (see, for example, the works of Allaire et al and Wang et al). Better representations at the cost of a more involved implementations are achieved by remeshing or discontinuous enrichments like those provided by the extended FEM . For the particular case of design‐dependent loads, this last alternative was used in the works of Jenkins and Maute (fluid‐solid interaction) and Coffin and Maute (thermal conduction problems).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we adopt a Lagrange multiplier approach, similar to the one of Geniaut et al (2007), for modeling sliding contact problems assuming a linear elastic material behavior and infinitesimal strains. The particular framework for integrating the explicit LSM and the generalized formulation of the XFEM used in this study are described in detail in Makhija and Maute (2014) and Villanueva and Maute (2014).…”
Section: Introductionmentioning
confidence: 99%